DIGNITY AND RELIGIOUS FREEDOM AS CONSUMER’S LAW - Snarski, Adam (Review of European and Comparative Law, 2018)
The article indicates the norms of law established in the European Union and Poland developed on the basis of the teachings of the Catholic Church, emphasizing the dignity and freedom of religious feelings, the consumer as a human being. The issue has been compared with the controversial advertising campaigns that broadly use religious beliefs of consumers in order to increase their effectiveness. The stimulus to discuss this issue is the intensification of controversial advertisements using religious symbols and cults. This publication also points out the issue of offense of religious feelings in advertising and draws attention to the normative areas of their protection.